Perencanaan Komunikasi Publik Pemerintah Kota Medan Dalam Menjalankan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) - Putri Fatimah; Grace Silalahi; Abdul Halim; Dedi Sahputra (Universitas Medan Area, 2022)
This study aims to determine the description of the Medan City government's public communication planning in carrying out the Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) in the midst of the COVID-19 pandemic. In this study, using the library research methods and a Content Analysis approach model that is an in-depth discussion of the contents of a written information so that the results of the Medan City Government succeeded in planning and communicating to the people of Medan City regarding how the government and the community to suppress the rate of spread of the COVID-19 Virus with the Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) as stated in the Instruction of the Minister of Home Affairs Number: 12 of 2001 concerning the Pemberlakuan Pembatasan KegiatanMasyarakat Mikro.